Examining Digital Government Maturity Models: Evaluating the Inclusion of Citizens - Åsa Waara (Administrative Sciences)
Digital transformation affects nearly every sector of society and is seen as a strategic approach to addressing evolving demands, including those of citizens, demographic shifts, and skill shortages. To tackle these challenges, governments have begun shifting from a government-centric to a citizen-centric approach, tailoring e-services to citizens’ life events and actively involving them in decision-making processes. Digital government maturity models (DGMMs) are essential tools for assessing digital readiness and guiding transformation, but their attention to citizen-centricity varies significantly. This study examines 18 DGMMs, revealing that 17% do not mention citizens, 33% reference them minimally, and only 50% integrate citizen considerations extensively. This research identifies seven themes where citizens were explicitly addressed in the DGMM, and these themes are maturity stages, areas of focus, enablers, constraints, metrics, insights, and recommendations. Despite the increased policy emphasis on citizen-centricity, gaps remain in translating this into actionable frameworks within DGMMs. This research contributes a thematic matrix and actionable insights to advance citizen-centric approaches, fostering public value creation, transparency, and trust. The findings offer guidance for researchers and practitioners to develop improved frameworks that align digital transformation efforts with citizens’ needs, ensuring inclusive and effective public sector transformation.